Xanthoma Tendinosum And Familial Hypercholesterolemia - Mahajan Vikram K; Sharma N. L; Sood Sandeep (Wolters Kluwer Medknow Publications, 2003)
A 40 year old female presented with multiple tendon xanthomas over extensor tendons of hands and feet, xanthelasma palpebrarum, arcus corneae and early atherosclerosis of retinal vessels. Investigations revealed normal triglycerides, very high plasma cholesterol and LDL levels, consistent with familial hypercholesterolemia (Fredrickson type lla). A work-up for cardiovascular involvement was normal and biopsy from one of the nodules showed xanthoma cells.